ASSISTANCE STRATEGY OF THE SURABAYA CITY OFFICE OF COOPERATIVES, SMALL AND MEDIUM ENTERPRISES AND TRADE (DINKOPUMDAG) IN IMPROVING THE SUSTAINABILITY OF MSME BUSINESSES IN DUKUH SETRO VILLAGE - Berlian Shafa Aldira Putri; Rusdi Hidayat Nugroho (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research aims to determine the impact of MSME and home industry assistance carried out by students during the internship program at the Surabaya City Small and Medium Enterprises Cooperative and Trade Office (Dinkopumdag), precisely in Dukuh Setro Village. In the Certified Independent Study Internship (MSIB) program as MSME assistants, students become an extension of the Surabaya City Dinkopumdag who are tasked with providing assistance to their fostered MSMEs. This research focuses on the strategies applied by the Cooperative and MSME Agency assistants, the challenges faced in mentoring, and the impact of mentoring on the sustainability of MSME businesses in Dukuh Setro Village. This research uses primary data collection techniques with observation and field interviews related to business conditions and constraints. Literature review also used in this study in order to support the data that has been obtained. The object of the research is MSMEs in Surabaya assisted by Dinkopumdag with a sample of 10 MSMEs in the food and beverage sector in Dukuh Setro Village, Surabaya. The results of the assistance in this study include digital marketing, branding, making legality and simple financial bookkeeping for MSMEs.